Zinc phosphate as a definitive cement for implant-supported crowns and fixed dentures - Flanagan D (Dove Medical Press, 2017)
Dennis Flanagan Private Practice, Willimantic, CT, USA Abstract: Implant-supported dental prostheses can be retained by a screw or cement. Implant-supported fixed partial dentures have a passive fit. A passive fit means there is an internal gap between the abutment surface and the intaglio of the retainer to insure that there is no lateral pressure on the supporting implants or friction upon seating of the prosthesis. This gap is filled with cement for retention of the prosthesis. Any lateral pressure may cause marginal bone loss or periimplantitis. Also, there is usually a microscopic gap at the margin of a crown retainer that exposes the cement to oral fluids. The solubility of zinc phosphate (ZOP) cement is a definite liability due to the risk for cement dissolution. In fixed prostheses, the dissolution of the cement of one or more retainers would cause a transfer of the occlusal load to the retained unit(s). The resulting rotation and lifting of the cement-retained implants from occlusal and parafunctional loads could cause loss of osseointegration of the abutment-retained implant(s). ZOP cement may not be indicated for implant-supported fixed partial dentures or splints. Cement dissolution in single unit probably only involves re-cementation, if the patient does not swallow or aspirate the crown. Keywords: passive fit, retention, film thickness, fixed, marginal gap